1969
DOI: 10.1080/00288233.1969.10427078
|View full text |Cite
|
Sign up to set email alerts
|

Grazing interval, stocking rate, and pasture production

Abstract: ABSTRACfData are presented to show that, under the same grazing management (a 7-day rotation), increasing stocking rate from 10 ewes/ac. to 15 ewes/ac. reduced pasture dry matter production. At the same high stocking rate (15 ewes/ac.), however, almost 50% more pasture D.M. was produced when a slow grazing rotation (28 days) was employed compared with a fast (7 days) rotation, and the stocking rate depression in pasture production was more than regained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

1974
1974
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
7
1
Order By: Relevance
“…Depressions in pasture production under high stocking similar to those measured in Years 1 and 3 of this trial have been reported by Campbell (1969) and Joyce (1970). The significantly higher production from the high-stocked than from the low-stocked pastures in Year 5 is considered to be the result of a change in experimental technique.…”
Section: Pasture Dm Productionsupporting
confidence: 86%
See 1 more Smart Citation
“…Depressions in pasture production under high stocking similar to those measured in Years 1 and 3 of this trial have been reported by Campbell (1969) and Joyce (1970). The significantly higher production from the high-stocked than from the low-stocked pastures in Year 5 is considered to be the result of a change in experimental technique.…”
Section: Pasture Dm Productionsupporting
confidence: 86%
“…Joyce (1970) found that pasture dry matter (DM) from ryegrass-white clover pastures was increased under a combination set-stocking and rotational-grazing management system when the stocking rate was 24 ewes/ha rather than 19 or 29 ewes/ha. Campbell (1969) reported a depression in pasture production under rotational grazing when the stocking rate was increased from t Present address: Ruakura Agricultural Research Centre, P.B., Hamilton, New Zealand. 24 ewes/ha to 36 ewes/ha.…”
Section: At Marton Elliottmentioning
confidence: 99%
“…The following year, which was the second full grazing year of the sward, the situation was reversed and the high stocking rate grew more grass than the medium, with the difference occurring during the summer months. The absence of a consistent reduction of grass production by a high stocking rate is contrary to the experience of Campbell (1969) with sheep and to the findings for February lambing (Orr and Newton, 1984). Frame (1975).…”
Section: Animal Performancecontrasting
confidence: 78%
“…Boswell (1977) found that cocksfoot needed a longer spell than ryegrass, unless it was grazed laxly. Some work eg Matches (1966) suggested that short spells were acceptable provided defoliation was not cióse, but other authors eg Morris (1969), and Campbell (1969) have demonstrated reduced green herbage production due to the dead material build up associated with lax defoliation. However these results and many like them have been found difficult to apply in practice.…”
Section: The Search For Guidelinesmentioning
confidence: 99%
“…At this stage individual tillers are so small that even the high efficiency of the youngest leaves cannot compénsate for reduced leaf área (Leafe and Parsons, 1983) and tillers die probably because of insufficient substrate to maintain respiraron. At low stocking rates productivity is reduced by the increase of dead material in the canopy, which shades green leaves, and tiller bases (Campbell. 1969), and also by the reduced efficiency of carbón dioxide fixation of leaves initiated and emerging in the sha- de of a tall canopy (Woledge, 1977).…”
Section: Reason For Reduced Production At High or Low Stocking Ratementioning
confidence: 99%